902 Reduced readmission rates through multidisciplinary, whole person care. (21st November 2017) - Zozaya-Monohon, Mary; Corona, Andrea
Abstract : Background: Readmissions are a surrogate marker for a patient's ability to manage their health. Ambulatory care is poised to transform services by partnering with patients to enhance their success with disease management to reduce hospitalizations. Objectives: Empower patients to optimise whole person, self-care with the support of a multidisciplinary team. Methods: A target population was selected after analysis of hospitalised and readmitted patients to confirm findings reported in the literature. A multidisciplinary team developed goals and objectives for whole person care to provide the framework for interventions. A process for identification, enrollment and discharge from the team was created. During team meetings patient needs are prioritised and integrated services are coordinated. The electronic medical record supports communication to the primary care provider and other members of the healthcare team. Results: The median readmission rate at baseline was 28% and decreased to 10% post implementation. This reduction in readmissions was obtained by implementing the intervention in 20% of all admitted patients. Interventions were assessed at baseline in all discharged patients compared to post-implementation target population. Completion of Physician's Orders for Life-Sustaining Treatment (POLST) rose from 9% to 41%, Personal Health Questionnaire-9 and Generalised Anxiety Disorder screening significantly increased to 94%. Evaluation by behavioural health and a pharmacist improved to 100%. Conclusions: Readmission rates can be decreased through ?coordinated, whole person interventions on a targeted patient population in the ambulatory setting. Implementing multidisciplinary proactive planned care improves a patient's ability to care for themselves as demonstrated by a reduced readmission rate.